STRATEGI PELAKSANAAN INTERVENSI GIZI SPESIFIK DALAM RANGKA PERCEPATAN PENURUNAN KONDISI STUNTING - JAMALUDDIN; Samsuddin; Andika (Badan Penelitian dan Pengembangan Daerah Kab. Pelalawan, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term, resulting in impaired growth in children. Stunting is also one of the causes of stunted children's height, so that it is lower than children of their age. Based on the explanation above, the formulation of the problem for this research study is how to carry out nutritional interventions for toddlers who are likely to experience stunting and what things can be done to prevent stunting in toddlers. The research study carried out in this study is a literature study or the materials needed in this study come from data that has reliable sources and can be proven valid. The findings of this study are that the way to carry out nutrition interventions for toddlers who are likely to experience stunting is to carry out nutritional assessments, nutritional diagnoses, nutritional interventions and nutritional monitoring and evaluation. Things that can be done to prevent stunting in toddlers are to pay attention to the condition and adequacy of nutrition that enters the mother's body during pregnancy and breastfeeding, provide exclusive breastfeeding until the baby enters the age of 6 months, accompany breastfeeding with healthy complementary foods and carry out health monitoring of the baby newborn to enter the age of 1,000 days of life in the world.